A methodology for enhancing implementation science proposals: comparison of face-to-face versus virtual workshops. (December 2015) - Marriott, Brigid; Rodriguez, Allison; Landes, Sara; Lewis, Cara; Comtois, Katherine
Abstract Background With the current funding climate and need for advancements in implementation science, there is a growing demand for grantsmanship workshops to increase the quality and rigor of proposals. A group-based implementation science-focused grantsmanship workshop, the Implementation Development Workshop (IDW), is one methodology to address this need. This manuscript provides an overview of the IDW structure, format, and findings regarding its utility. Results The IDW methodology allows researchers to vet projects in the proposal stage in a structured format with a facilitator and two types of expert participants: presenters and attendees. The presenter uses a one-page handout and verbal presentation to present their proposal and questions. The facilitator elicits feedback from attendees using a format designed to maximize the number of unique points made. After each IDW, participants completed an anonymous survey assessing perceptions of the IDW. Presenters completed a funding survey measuring grant submission and funding success. Qualitative interviews were conducted with a subset of participants who participated in both delivery formats. Mixed method analyses were performed to evaluate the effectiveness and acceptability of the IDW and compare the delivery formats. Of those who participated in an IDW (N = 72), 40 participated in face-to-face only, 16 in virtual only, and 16 in both formats. Thirty-eight (face-to-facen = 12, 35 % response rate; virtualn = 26, 66.7 % response rate) responded to the surveys and seven (15.3 % response rate), who had attended both formats, completed an interview. Of 36 total presenters, 17 (face-to-facen = 12, 42.9 % response rate; virtualn = 5, 62.9 % response rate) responded to the funding survey. Mixed method analyses indicated that the IDW was effective for collaboration and growth, effective for enhancing success in obtaining grants, and acceptable. A third (35.3 %) of presenters ultimately received funding for their proposal, and more than 80 % of those who presented indicated they would present again in the future. The IDW structure and facilitation process were found to be acceptable, with both formats rated as equally strong. Conclusions The IDW presents an acceptable and successful methodology for increasing competitiveness of implementation science grant proposals.